LABEL HALAL, KESADARAN HALAL , RELIGIUSITAS DAN MINAT BELI PRODUK KOSMETIK HALAL - Budi Suryowati; Nurhasanah Nurhasanah (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
This study aims to determine the effect of halal labels, halal awareness and religiosity on the interest in buying halal cosmetics. This study was conducted on Muslim women, aged 17-30 years, using halal cosmetics in DKI Jakarta. The number of samples taken in the study of 100 respondents with non probability purposive sampling techniques, data collected through questionnaires. The analytical method uses the Structural Equation Modeling (SEM) equation with SmartPLS 3.0 software. The results showed that the halal label did not significantly influence the buying interest of halal cosmetics while religious religiosity and halal awareness had a significant effect on the purchase intention of halal cosmetics.